Antesenden dari Customer satisfaction pada Online Travel Service - Muhammad Kevin Humala Sakti Siregar; Luki Adiati Pratomo (Universitas Darussalam Gontor, 2020)
The aim of this research was to investigate the influence of perceived usability and perceived usefulness to customer satisfaction in online travel service. The samples used are 217 responses which using online travel service. Dependent variable in this research are customer satisfaction. Independent variable is perceived usability and perceived usefulness. Analysis method in this research is SEM. The result of this research shows that perceived usability and perceived usefulness have positif influence toward customer satisfaction.